(untitled) (Docentes 2.0 Journal, 2021)
Educational research is paying greater attention to school engagement in recent years. It has become a valuable tool for analyzing the relationship of students with their schools, as well as their degree of engagement with them. School engagement, as a measurement tool, provides valuable data for the understanding of how this engagement develops and what variables affect it. In addition, it has been thoroughly confirmed as an excellent indicator of future complications, including school dropout. Despite these successes, an important element of the research, the school context in which the data was collected, has traditionally been ignored. Some data concerning the characteristics of the center (socioeconomic level, place, age of the students ...) have been considered. However, the events occurring within the walls of the school have been regularly ignored. Thus, this essay argues that the data on school engagement should be supported by knowledge of the school’s culture. Otherwise, any attempt to understand or justify engagement, not knowing the concrete reality or the school’s culture, will be based on theories and hypotheses that may be far from the real context. In this essay, a new approach of study is proposed. It highlights the need to value school culture as a key concept to understand school engagement. In addition, a novel model containing seven variables is presented, where school engagement and the school environment (school culture) are studied together. This model will provide the necessary data to establish cause-effect relationships and the formulation of adequate hypotheses.